2016
DOI: 10.3945/jn.116.231803
|View full text |Cite
|
Sign up to set email alerts
|

Protein Supplementation Has Minimal Effects on Muscle Adaptations during Resistance Exercise Training in Young Men: A Double-Blind Randomized Clinical Trial

Abstract: Background: To our knowledge the efficacy of soy-dairy protein blend (PB) supplementation with resistance exercise training (RET) has not been evaluated in a longitudinal study.Objective: Our aim was to determine the effect of PB supplementation during RET on muscle adaptation.Methods: In this double-blind randomized clinical trial, healthy young men [18–30 y; BMI (in kg/m2): 25 ± 0.5] participated in supervised whole-body RET at 60–80% 1-repetition maximum (1-RM) for 3 d/wk for 12 wk with random assignment to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 47 publications
(60 reference statements)
7
70
0
1
Order By: Relevance
“…There were no differences between treatments at pre for any of the descriptive characteristics (p>0.10). As our previous report indicated (38), the habitual protein intake for participants was ∼1.3 g/kg/d and the participants increased protein intake in both protein supplement groups above this level.…”
Section: Methodssupporting
confidence: 64%
See 3 more Smart Citations
“…There were no differences between treatments at pre for any of the descriptive characteristics (p>0.10). As our previous report indicated (38), the habitual protein intake for participants was ∼1.3 g/kg/d and the participants increased protein intake in both protein supplement groups above this level.…”
Section: Methodssupporting
confidence: 64%
“…Participant were of similar age (PB: 24.1±0.6; WP: 24.6±1.0; MDP 25.2±1.1), height (PB: 178.6.1±1.5; WP: 180.0.6±2.1; MDP 176.0±1.6) weight (PB: 77.51±2.3; WP: 83.5±3.4; MDP 76.3±1.3), BMI (PB: 24.3±0.6; WP: 25.7±0.9; MDP 24.5±0.8), whole body lean mass (PB: 56.2±1.3; WP: 58.9±2.3; MDP 55.4±1.7), and leg lean mass (PB: 19.0±0.4; WP: 20.7±1.0; MDP 18.7±0.8) at pre. The subjects included in this study were a subset of a larger clinical trial (38), where screening and enrollment details can be found alongside information concerning treatment compliance, dietary intake and strength testing. There were no differences between treatments at pre for any of the descriptive characteristics (p>0.10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, a systematic review and meta-analysis that included 15 placebo-controlled treatment groups with baseline and ending measures and an additional 32 reports involving 36 treatment groups found no effects of soy protein or isoflavone intake on testosterone, sex hormone binding globulin, free testosterone or the free androgen index [283]. Studies published subsequent to this meta-analysis have reached similar conclusions [168,392,393,394]. The two aforementioned case reports simply illustrate that consuming excessive amounts of essentially any food can potentially lead to abnormalities [389,390].…”
Section: Male Feminizationmentioning
confidence: 72%